Development of Host Immune Response to Bacteriophage in a Lung Transplant Recipient on Adjunctive Phage Therapy for a Multidrug-Resistant Pneumonia - Dan, Jennifer M; Lehman, Susan M; Al-Kolla, Rita; Penziner, Samuel; Afshar, Kamyar; Yung, Gordon; Golts, Eugene; Law, Nancy; Logan, Cathy; Kovach, Zsuzsanna; Mearns, Gill; Schooley, Robert T; et al. (The Journal of infectious diseases, 2023)
Bacteriophage therapy is the use of viruses to kill bacteria for the treatment of antibiotic-resistant infections. Little is known about the human immune response following phage therapy. We report the development of phage-specific CD4 T cells alongside rising phage-specific immunoglobulin G and neutralizing antibodies in response to adjunctive bacteriophage therapy used to treat a multidrug-resistant Pseudomonas aeruginosa pneumonia in a lung transplant recipient. Clinically, treatment was considered a success despite the development phage-specific immune responses.